Team; Front cover, Editorial information, Table of Content, Back Cover, - Journal Editor (Journal of Tropical Pharmacy and Chemistry, 2010)
J. Trop. Pharm. Chem. 2010. Volume 1 Nomor 1 Team; Front cover, Editorial information, Table of Content, Back Cover